Understanding dynamics of social relationships among college students: a sociometric approach - Mohammed Najar, Sabah Ahmed; Ahmed, Taban Khalid (Penerbit Universiti Kebangsaan Malaysia, 2020)
Social relations of students are active and effective relating to social factors. This study explores what factors determine dynamics of student relationships. This study focused on quantitative and qualitative approaches, especially sociometry as the main method of analysis, which emphasis observation, interview, and questionnaire. The study performed in the College of Art – University of Slemani with 37 students who were at their second, third and fourth years in the Department of Drawing. A sociomatrix and sociometric indexes were used to analyze the data, and the results showed that effect of students on each other in class, social interactions, and strength of social relations significantly affected the dynamics of relationship. Students have effects power for others within class. For social interaction, relationships are active in which students mostly interact with each other. For strength of students, there are positive, reaction and social adjustment in students’ relationships. Therefore, results concluded that relationship of students has dynamics. The implication of this study is that dean and academic staff of Art college should try to keep and continue dynamic of students’ relationship through opening art gallery participating all students, organizing art activities, supporting students to do teamwork.